TELAAH KEPASTIAN HUKUM TERHADAP MASA TUNGGU TERPIDANA MATI PADA PENGAJUAN UPAYA HUKUM LUAR BIASA - Frendi Setiawan; Muhammad Rustamaji (Verstek, 2025)
This article discusses the certainty of the waiting period for death row inmates before the enactment of Law Number 1 of 2023 concerning the Criminal Code (New Criminal Code) as well as the time period for submitting extraordinary legal remedies such as pardon and review of decisions that have been inkracht as a form of grant. human rights before the death penalty is executed. This type of research is normative legal research that is descriptive in nature with secondary data types including primary and secondary legal materials. The technique for collecting legal materials is carried out by literature study, then the analytical technique used is the deductive method. This research resulted in regulations regarding the waiting period for death row inmates before the enactment of the new Criminal Code which still does not provide certainty regarding the deadline for submitting a review as regulated in Article 264 paragraph 3 of the Criminal Procedure Code (KUHAP) and Decision Number 107/PUU-XIII/2015 Regarding the application for a period of clemency, this results in the lack of legal certainty regarding the execution of the death penalty because it requires an unlimited amount of time to fulfill the rights of the convict.